Subcortical Intermittent Theta-Burst Stimulation (iTBS) Increases Theta-Power in Dorsolateral Prefrontal Cortex (DLPFC) - Bentley, J. Nicole; Irwin, Zachary T.; Black, Sarah D.; Roach, Megan L.; Vaden, Ryan J.; Gonzalez, Christopher L.; Khan, Anas U.; El-Sayed, Galal A.; Knight, Robert T.; Guthrie, Barton L.; Walker, Harrison C. (Frontiers in Neuroscience, 2020)
Introduction: Cognitive symptoms from Parkinson’s disease cause severe disability and significantly limit quality of life. Little is known about mechanisms of cognitive impairment in PD, although aberrant oscillatory activity in basal ganglia-thalamo-prefrontal cortical circuits likely plays an important role. While continuous high-frequency deep brain stimulation (DBS) improves motor symptoms, it is generally ineffective for cognitive symptoms. Although we lack robust treatment options for these symptoms, recent studies with transcranial magnetic stimulation (TMS), applying intermittent theta-burst stimulation (iTBS) to dorsolateral prefrontal cortex (DLPFC), suggest beneficial effects for certain aspects of cognition, such as memory or inhibitory control. While TMS is non-invasive, its results are transient and require repeated application. Subcortical DBS targets have strong reciprocal connections with prefrontal cortex, such that iTBS through the permanently implanted lead might represent a more durable solution. Here we demonstrate safety and feasibility for delivering iTBS from the DBS electrode and explore changes in DLPFC electrophysiology. Methods: We enrolled seven participants with medically refractory Parkinson’s disease who underwent DBS surgery targeting either the subthalamic nucleus (STN) or globus pallidus interna (GPi). We temporarily placed an electrocorticography strip over DLPFC through the DBS burr hole. After placement of the DBS electrode into either GPi (n=3) or STN (n=4), awake subjects rested quietly during iTBS (three 50-Hz pulses delivered at 5 Hz for 2 seconds, followed by 8 seconds of rest). We contrasted power spectra in DLPFC local field potentials during iTBS versus at rest, as well as between iTBS and conventional high-frequency stimulation (HFS). Results: Dominant frequencies in DLPFC at rest varied among subjects and along the subdural strip electrode, though they were generally localized in theta (3-8 Hz) and/or beta (10-30 Hz) ranges. Both iTBS and HFS were well-tolerated and imperceptible. iTBS increased theta-frequency activity more than HFS. Further, GPi stimulation resulted in significantly greater theta-power versus STN stimulation in our sample. Conclusion: Acute subcortical iTBS from the DBS electrode was safe and well-tolerated. iTBS in the GPi may increase theta-frequency power in ipsilateral DLPFC. Future studies will evaluate whether these changes are associated with improvements in cognitive or behavioral symptoms from PD.